Alzheimer's disease and type 2 diabetes: Two diseases, one common link?. (April 2013) - Bartl, Jasmin; Monoranu, Camelia-Maria; Wagner, Anne-Kristin; Kolter, Jann; Riederer, Peter; Grünblatt, Edna
Abstract: Objectives. Although Alzheimer's disease (AD) is the most common form of dementia in the elderly, its aetiology remains mostly unknown. A potential pathophysiological mechanism for AD arises from the knowledge that insulin is also synthesized independently in the central nervous system and is involved in the regulation of memory formation. AD may represent a brain-specific form of insulin resistance. Methods . We used immunohistochemistry to investigate the numbers of cells expressing insulin receptor β-subunit (IRβ) and phosphorylated PPARγ (PPARγ(p)) in human post-mortem tissue from patients with AD; AD combined with type 2 diabetes mellitus (T2DM); just T2DM, and from aged-matched controls. These numbers were evaluated in frontal cortex and in dorsal/ventral parts of the hippocampus. Results. We observed significantly lower numbers of IRβ positive cells in AD cases compared to all other groups in all investigated brain regions. Also significantly more PPARγ(p) positive cells occurred in each patient group compared to control. Conclusions . T2DM and AD may not be directly linked, but may share common histological features including lower numbers of IRβ positive cells and higher numbers of PPARγ(p) positive cells in all investigated brain regions. These observations may at least partially explain the increased frequency of AD in elderly diabetic patients.